Study of a series of fluorophore-labeled artesunate derivatives – Design, analysis and application. (November 2017) - Yang, Zihao; Ge, Guangbo; Liu, Fengyu; Chen, Su-Shing; Sun, Shiguo
Abstract: Artesunate (ART) is an antimalarial and potential anticancer drug which exerts diverse physiological and pathological functions. Unfortunately, the detailed mechanisms of operation of ART derivatives still remain elusive. To solve this, modification of ART with fluorophores can be a good choice. However, whether the modification has any influence on the drug itself is still a problem that remains to be solved. Herein, three different fluorophores (anthracene (E ), pyrene (B ) and naphthalimide (N )) were designed and synthesized to covalently link with ART to get three fluorophore-labeled ART derivatives (AE, AB andAN ). The result demonstrated that the spectral characteristics of these derivatives was not affected by different fluorophores. While, AN cannot be hydrolyzed by the most common drug metabolism enzymes like human liver microsomes (HLM), rat liver microsomes (RLM) and mouse liver microsomes (MLM). In comparison, AE andAB can be hydrolyzed much easier thanAN, leading to the release of ART. Co-localization studies suggest thatAN exhibited superior lysosome-targeting ability thanAE andAB, due to the preferential accumulation of ART in lysosome and the remarkable enzyme hydrolysis stability ofAN . Furthermore, not much cytotoxicity was observed for the corresponding fluorophore-labeled ART derivatives compared with that of ART alone. Graphical abstract: Three different fluorophores were introduced to ART to study whether the modification has any influence. Highlights: Different fluorophores were designed and synthesized to covalently link with ART to get three ART derivatives. AN can be used as lysosome locating probe whileAE andAB can be acted as potential labeling tool to monitor ART release. Providing some suggestions for drug modification related work later.